Inappropriate defibrillator shocks and mortality - Liew, Reginald (Heart (British Cardiac Society), 2013)
[...]66% of subjects in the MADIT II study had a New York Heart Association (NYHA) functional class between 2 and 4 ,and 30.5% of subjects in the SCD-HeFT study were in NYHA class 3, whereas only 7.8% of subjects in the study by Deyell et al 11 with inappropriate shocks were in NYHA class 3-4. [...]although the study by Deyell et al 11 included patients with ICD implanted for secondary prevention, the subjects may have been less sick (as evidenced by a better NYHA class compared to the primary prevention studies), which may partly explain why inappropriate shocks did not appear to affect mortality adversely in this heart failure population.